Inventing American exceptionalism - Kessler, Amalia D. (New Haven : Yale University Press, 2017)
It is widely accepted that American procedure - and indeed American legal culture as a whole - are adversarial (and distinctively so). Yet, precisely because this assumption is so deep-rooted, we have no history of how American adversarialism arose. This text provides such a history. It shows that the United States long employed not only lawyer-empowering adversarial procedure, but also various forms of more judge-dependent, quasi-inquisitorial procedure - including the equity tradition borrowed from England and, to a lesser extent, conciliation courts transplanted from continental Europe.
Previously issued in print: 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on April 3, 2017).
Keywords: Adversary system (Law) -- United States; Law -- United States -- History -- 19th century; Law; United States of America, USA; 19th century, c 1800 to c 1899.; History of the Americas; History; Legal history